Ovarian hyperstimulation syndrome and pulmonary edema – a rare complication - Mishra, Vineet; Roy, Priyankur; Choudhary, Sumesh; Aggarwal, Rohina; Hokabaj, Shaheen; Saini, Suwa Ram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian Hyperstimulation Syndrome (OHSS) is a life-threatening complication of controlled ovarian stimulation almost exclusively associated with gonadotropins but occasionally with clomiphene citrate. Prevention of this syndrome lies in the recognition of risk factors and individualizing the treatment regimens. Causes of respiratory distress in patients with OHSS are pleural effusion, pulmonary embolism, and acute respiratory distress syndrome (ARDS). Pulmonary edema is rare but a grave complication of OHSS. Case report: We report, a case of severe OHSS with tense ascites and anasarca after controlled ovarian hyperstimulation (COH) for IVF. She was managed conservatively followed by paracentesis after which she developed pulmonary edema during the course of the treatment. Conclusion: OHSS is an iatrogenic complication which can be prevented by individualizing stimulation protocols and should be managed urgently with a multidisciplinary approach.